(untitled) (Bangladesh Journal of Medical Science, 2022)
Background/aim: Occupational stress is one of the major problems of nurses that can have negative effects on their job performance. Since stress is unavoidable, it is necessary to use methods to reduce or control and manage it in nurses. The purpose of this study was to determine the effectiveness of coping strategies training on nurses’ occupational stress in Jahrom hospitals. Materials and methods: This quasi-experimental study with two groups of experimental and control was randomly selected from nurses working in internal and surgical wards and divided into two groups of 25 each. Demographic information questionnaire and OSIPOW Occupational stress questionnaire were used to measure nurses’ job stress in both groups. The experimental group received 4 sessions of 90 minutes in the framework of the coping strategies workshop and the control group did not receive any training. Finally, to assess the effect of intervention, one month after the sessions, the questionnaires were completed by the control andexperimental groups again. Results: The mean scores of nurses’ Occupational stress in the pre- and post-test groups were 180.12±19.52 and 166.28± 25.71, respectively. The mean score of nurses’ Occupational stress in the control group before and after the test was 178.08±24.65 and 178.95±22.14, respectively. Results showed a decreasing trend of job stress score in the experimental group (P = 0.02), while no significant change was observed in the control group score. Conclusion: Coping strategies training is effective in reducing nurses’ Occupational stress and it can be recommended to reduce other stressful occupations. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 354-360